A polinização e as abelhas: uma sequência didática para o ensino de ciências nos anos iniciais do ensino fundamental - Silveira, Maira dos Santos (2023)
Teaching science to children means enabling them to explore the environment in which they live. From this point of view, the school environment must be stimulating and enable this interaction. It must be backed up by a proposal to build knowledge, stimulating reflection and discussion. This dissertation aimed to investigate, through a sequence of activities in different educational spaces, the construction of knowledge about the importance of bees in the pollination process with Early Years students. The research had a qualitative approach and the procedure adopted was a case study. It was carried out with 89 students from the 2nd to the 5th year of primary school at a public school in the interior of the state of Rio Grande do Sul - Brazil. The initial stage, which involved studying the students' preconceptions, contributed to the development of a Didactic Sequence (DS) on pollination and the importance of bees. A semi-structured questionnaire was used for this study, and field notes and drawings developed during the activities were used to validate the DS, which were subjected to a posteriori categorization. The initial results of the previous conceptions showed fragmentation on the subject. The students related bees to the production of honey, their ability to sting and make pollen. In their speeches and answers, they did not distinguish between honey, pollen and nectar. With regard to pollen, they replied that they didn't know, and also described it as the yellow part of the flower that bees pick up to make honey. Regarding pollination, the students didn't know what to think about pollination. When we showed them images of pollinators in flowers, the students referred to feeding, but not to pollination. They found it difficult to identify some pollinating agents because they were feeding and pollinating, as was the case with the blowfly on the flower. In relation to the process of pollination, they infer that they have no idea how it happens, and some students tried to construct some idea of association "bees taking pollen to make honey". After the Didactic Sequence was developed, in different educational spaces, the students highlighted the Pollination Trail as the most relevant activity, since it was applied in a natural environment. The analysis of the drawings on pollination showed, significantly, that the second and third year students recognized the pollination process in a simpler way, but one that was appropriate for their age group, and the fourth and fifth year students demonstrated an understanding of the pollination process, reproduction and fruit formation. After the activities, the students were able to point out different types of pollinators, such as hummingbirds, butterflies, wasps, flies, bats and, above all, bees. They also pointed out the importance of pollinators. The students emphasized the importance of bees, demonstrating their understanding of the importance of these insects to the ecosystem. The data indicated a real and consistent possibility of gaining knowledge of the students' previous conceptions in order to develop didactic sequences aimed at the Early Years of Primary School as mediators of learning in science teaching.